Effect of oral and transdermal oestrogen therapy on bone mineral density in functional hypothalamic amenorrhoea: a systematic review and meta-analysis. Issue 3 (7th July 2021) - Aalberg, Karoline; Stavem, Knut; Norheim, Frode; Russell, Michael Bjørn; Chaibi, Aleksander
Abstract : Background: Female athletes might develop reduced bone mineral density (BMD) and amenorrhoea due to low energy intake. Objective: To systematically review the literature of randomised controlled trials (RCTs) assessing the effect of oestrogen oral contraceptives (OCP), conjugated oestrogens (CE) and transdermal estradiol (TE) on BMD in premenopausal women with functional hypothalamic amenorrhoea (FHA) due to weight loss, vigorous exercise and/or stress. Methods: A comprehensive literature search in PubMed, MEDLINE, Cochrane Library, Ovid and CINAHL from inception to 1 October 2020. Data extraction and synthesis: Two authors independently extracted data. When possible, the data were pooled in a random-effects meta-analysis. Main outcomes: Difference in BMD (g/cm 2 ) at the lumbar spine. Results: Nine RCTs comprising 770 participants met the inclusion criteria; five studies applied OCP, two CE and two TE. Four RCTs (two OCP, two TE) found an increased BMD in premenopausal women with FHA, and five (three OCP, two CE) found a decreased BMD compared with controls. A meta-analysis showed no difference in BMD between the treatment and control groups, (standardised mean difference (SMD) 0.30, 95% CI −0.12 to 0.73). A secondary analysis for change scores from baseline to first assessment point, showed a similar overall result (SMD 0.17, 95% CI −0.16 to 0.51). No serious adverse events were reported. Conclusion: The literature suggests that TE might increase lumbar BMD in premenopausal women with FHA, but pooled results revealed no effect of the intervention. The findings do not support oestrogen therapy to improve BMD in these patient groups.